Attribute-based encryption scheme with efficient revocation in data outsourcing systems - Xi-xi YAN; Yong-li TANG (Tongxin xuebao)
In order to support fine-grained attribute revocation in data outsourcing systems,an attribute-based encryption scheme with efficient revocation in indirect revocation model was proposed.The model of ABE supporting attribute revocation was given,and a concrete scheme was constructed which proved its security under the standard model.Compared to the existing related schemes,the size of ciphertext and private/secret key is reduced,and the new scheme achieves fine-grained and immediate attribute revocation which is more suitable for the practical applications.